A numerical analysis of a fully penetrated encased granular column. Issue 5 (October 2017) - Hong, Yung-Shan; Wu, Cho-Sen; Kou, Chien-Ming; Chang, Cheng-Hsin
Abstract: This paper studies the performance of an individual encased granular column that is embedded in soft soil using a numerical analysis. The numerical analysis is verified by experimental tests that are performed in the laboratory, using a model encased sand column that is embedded in a soft clay deposit. In addition to bearing stress-settlement response, detailed characterizations of the encased column, in terms of the distribution of lateral earth and sleeve-induced pressure along the column length, are determined. The numerically analyzed results are compared with those for the model tests and analytical results. Parametric studies over the encasement stiffness, the diameter of the granular column and the loading area are conducted to determine the influence of encasement on the column. The sleeve-induced confining pressure and the bearing stress of the encased sand columns, calculated using the cavity expansion theory and the simplified approach that assumes a constant volume for the granular column, are compared with the numerical results to justify the use of these two methods. The numerical results show that the stiffness of the encasement significantly affects the bulging length of an encased granular column. An increase in the column diameter or the loading area produces a significant reduction in the sleeve-induced confining pressure, which leads to a reduction in the bearing stress improvement of an encased granular column, but the total load supported by the loading plate has an almost linear relationship with the loading plate diameter/column diameter ratio.